PENGELOLAAN LIMBAH MEDIS PADAT B3 DI PUSKESMAS PERAWATAN BETUNGAN KOTA BENGKULU TAHUN 2021 - Nurhayati, Hestika; Ramon, Agus; Febriawati, Henni; Wati, Nopia (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2021)
ABSTRACTÂ The Betungan Health Center in Bengkulu City has an outpatient and nursing service unit. The health services provided by the Puskesmas in Betungan in Bengkulu City can have a negative impact on the environment and the surrounding community. The general objective of this research is to know the implementation of the B3 solid medical waste management system at the Betungan Health Center, Bengkulu City. This type of research is a qualitative research with a descriptive approach. The research location was carried out at the Betungan Health Center, Bengkulu City in January-February 2021. Sources of informants were health care and cleaning service officers. Data collection techniques by means of interviews, observation and documentation. The results showed that the identification of B3 waste, Temporary Shelters (TPS) for solid B3 medical and further processing of B3 Solid Medical Waste at the Betungan Health Center were in accordance with Minister of Health Regulation No. 7 of 2019. Meanwhile, the sorting of B3 solid medical waste, the storage and transportation of B3 solid medical waste is not in accordance with Minister of Health Regulation No. 7 Years 2019 The conclusion from the results of the study that solid medical waste treatment at the Betungan Health Center in Bengkulu City was not in accordance with the Minister of Health Regulation No. 7 ofÂ 2019, because there are still some that do not meet the standards at the stages of selection, storage and transportation.